Challenges and Adaptive Strategies of Santals of Bnasbari Village of Rajshahi in Ensuring Healthcare - James Soren; Edward Soren; Jesus P Briones (Research Synergy Foundation, 2023)
Healthcare challenges for indigenous communities are one of the burning issues in Bangladesh and many other countries. Dishonor for indigenous communities and discrimination against them put them under challenges that affect their daily lives and extend to their healthcare. Since indigenous communities are a significant part of the overall population, their healthcare disparities raise questions about the country’s development. A real development of a country is not possible with a significant part excluded, and it may affect the country’s achieving the SDGs. However, existing literature lacks discussion on this special issue, so information regarding indigenous communities’ healthcare challenges and adaptive strategies is not available. Applying qualitative research methodology, this research found that Santals, a major indigenous community in Bangladesh, are excluded from healthcare because of the negligence and disrespectful attitudes of people in the Bengali community and the decline of medical plants and forest-like settings, which leads Santals to adopt different strategies in ensuring healthcare. This research also shows that Santals are taking allopathic medicines from village doctors, buying allopathic medicines without consulting with doctors, taking homeopathic medicines, taking traditional medicine plants by planting them in their homesteads, and buying medicines from street hawkers.